Vegetation Composition of the Succession Forest of Sumatran Orangutan (Pongo abelii) Habitat in Tropical Lowland Forest, Gunung Leuser National Park - Ardi, Rio; Onrizal; Thoha, Achmad Siddik; Mansor, Mashhor (Journal of Sylva Indonesiana, 2025)
The Gunung Leuser National Park (GLNP) area, among others, consist of tropical lowland-forest ecosystems that becomes the habitat of Sumatran orangutans (Pongo abelii). The GLNP is located at Aceh dan North Sumatra Provinces and lies on 830,268,95 hectares of land. To date, the area is not free from the pressure of forest degradation, such as encroachment and land conversion to plantations. This is a perturbing condition, especially concerning the biodiversity in its lowland-forest ecosystem. The vegetation composition that renders the succession of Sumatran orangutans in the GLNP lowland-forest was obtained by conducting vegetation analysis on the restoration sites in the forest. The analysis method adopted on this research was the grid-path method. Two transect lines, 1,000 metres each, were made for this purpose. Each line consisted of 10 plots with a distance of 100 metres between plots. The measurements were made on the growth rate of seedling, sapling, pole, and tree. The data were then processed to determine the Important Value Index (IVI), Diversity Index, Richness Index of vegetation, and Dominance Index of the research area. The results showed that the vegetation composition that rendered the succession of lowland-forests of GLNP consisted of 58 species and 26 families. Ficus fistulosa had the highest IVI at the growth-stages of seedling and sapling. And Macaranga tanarius had the highest IVI at the growth-stages of pole and tree. The species Diversity Index (Shannon-Wiener index) of the vegetation on the restoration site in lowland forests of GLNP showed moderate values at the growth-stage of seedling and pole, and high values at the growth-stages of sapling and tree. The Richness Index of vegetation showed moderate values at the growth-stages of seedling and pole. As for at the stages of sapling and tree, it showed high values. The Dominance Index of the restoration site in lowland forests of GLNP showed high values at all growth-stages.